Strengthening Economic Independence for People with Deaf Disabilities at SEHJIRA Foundation-Tangerang-Banten through Improving Entrepreneurship Skills in the Creative Economy Sector - Setyawan, Agus Budi; Hasni, Fatimah Yasmin; Syakina, Dina; Ananda, Aurelia; Mulya, Annisa Ananda (Jurnal Abdi Masyarakat (JAM), 2025)
SEHJIRA, a deaf foundation in Tangerang, Banten, faces various challenges in empowering deaf people, including low self-confidence, lack of creative economic skills, and lack of understanding about digital business. This Community Service Program is designed to address these issues with three main solutions: psychological training to build self-confidence, skills training in convection, screen printing, and tie-dyed batik to produce creative products, and business management and digital marketing training. The goal is to empower deaf people to become financially and emotionally independent through the creative economy sector. Lecturers and students collaborate in training that includes increasing self-confidence, production skills, and product marketing. The results showed an increase in self-confidence, skills in producing creative products, and the ability to market products digitally. Participants were enthusiastic and motivated to apply the training for economic independence. This program produced outcomes in the form of improved skills, production tools, scientific publications, and an increase in the positive image of the SEHJIRA Foundation.